Religious Literacy in Law: Anti-Muslim Initiatives in Quebec, the United States, and India. Issue 1 (2nd January 2021) - Amarasingam, Amarnath; Tiflati, Hicham; Walker, Nathan C.
Abstract: This inquiry examines how religious illiteracy amongst politicians, legislators, lawyers, and judges could lead to discriminatory legislations and increased persecution against religious minorities. We look at laws and legislations in three contexts, Quebec, the USA, and India, where anti-religious sentiments and violence are predominantly directed against Muslims. More specifically, we examine Quebec's legal attempts, in the form of exclusive laïcité, to regulate religion and religious signs within the province; the recent ruling about converting the Babri mosque in India into a Hindu Temple; and anti-Shariah laws in the United States. Taken together, these justifications for anti-Muslim bills perpetuated illiteracy about both religion and the legal systems, leading the conditions for discrimination against religious minorities. We conclude that religious illiteracy, more specifically on the level of judiciaries and legislative bodies, presents a pressing threat to the safety and wellbeing of religious minorities, Muslims in particular, around the world.